2020
DOI: 10.3390/en13082005
|View full text |Cite
|
Sign up to set email alerts
|

Space Charge Accumulation at Material Interfaces in HVDC Cable Insulation Part I—Experimental Study and Charge Injection Hypothesis

Abstract: On-site installation of accessories on extruded polymeric high voltage cables in a common practice. The procedure requires the shaping of the physical interface between the cable insulation surface and the pre-molded accessory body. On such interfaces, rough surfaces should be avoided in order to limit space charge accumulation in the insulation, which affects the cable performance by reducing insulation life-time, creating conditions for local field enhancement, and, respectively, the formation of possible br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…A bipolar charge transport model, already reported in the literature [5,[7][8][9], has been used for the simulations in a low density polyethylene (LDPE). This charge transport model, also called mesoscopic model in the literature for insulating polymers [10], is a hydrodynamic model, based on the advection equation. The model is one dimensional, function of the depth in the sample, and features generation of electronic charges (i.e.…”
Section: Model Descriptionmentioning
confidence: 99%
“…A bipolar charge transport model, already reported in the literature [5,[7][8][9], has been used for the simulations in a low density polyethylene (LDPE). This charge transport model, also called mesoscopic model in the literature for insulating polymers [10], is a hydrodynamic model, based on the advection equation. The model is one dimensional, function of the depth in the sample, and features generation of electronic charges (i.e.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Simulations have been performed with the 2D model, in order to observe the impact of surface roughness on the macroscopic space charge behaviour. Previous studies on the impact of surface roughness on electric field distribution [6,7] have shown that concave defects forming protrusions on the electrode enhance the electric field to a large extent. The field enhancement factor (FEF), i.e.…”
Section: Impact Of the Roughness Shapementioning
confidence: 99%
“…Charges, generated at the electrodes or inside the bulk, disturb the electric field distribution, leading to local field enhancements, and potentially to an early breakdown. Bipolar charge transport models, also called BCT or mesoscopic models [1][2][3], have been developed this last two decades to predict the electric field distribution within such insulating materials. Electronic charges generation (electrons or holes) at the electrodes are generally described as charge injection, either using the thermionic -i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Impact of nanometric processes linked to charge generation on the macroscopic behaviour in polyethylene Q.M. Hoang 1 and S. Le Roy 2 1 Faculty of Electrical Engineering, Hanoi University of Industry, Hanoi, Vietnam, 2 LAPLACE, Université de Toulouse, CNRS, INPT, UPS, Toulouse, France…”
mentioning
confidence: 99%